2023
DOI: 10.1002/csr.2452
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable development of supplier performance. An empirical analysis of relationship characteristics in the automotive sector

Abstract: Sustainability performance of suppliers has become increasingly important for both corporate practice and research. While the importance of relationships between the focal company and its suppliers has been acknowledged for improving sustainability performance of suppliers, little is known about the role of relation specific factors in practice. This research fills this gap by empirically analyzing the relevance of relationspecific factors for the sustainability performance of suppliers based on a unique data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 94 publications
0
2
0
Order By: Relevance
“…In this study, the SSEP scale was developed through the implementation of sustainability initiatives, sustainability reputation and the adoption of environmental management system practices through ISO 14001 certification. Previous literature has revealed that those metrics are positively related to supplier sustainability performance (Naffin et al, 2023; Yang & Zhang, 2017; Zimmer et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the SSEP scale was developed through the implementation of sustainability initiatives, sustainability reputation and the adoption of environmental management system practices through ISO 14001 certification. Previous literature has revealed that those metrics are positively related to supplier sustainability performance (Naffin et al, 2023; Yang & Zhang, 2017; Zimmer et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Beyond this, SSCM serves as an approach for buying firms to manage sustainability concerns with suppliers in the form of supplier evaluation for risk and performance (Hossan Chowdhury & Quaddus, 2021). To assess sustainability performance of suppliers, the most common tools suggested to buying firms are certifications, sustainability report and codes of conduct (Naffin et al, 2023). However, implementing SSCM requires more than just supplier evaluation.…”
mentioning
confidence: 99%
“…In this study, the SSEP scale was developed through the implementation of sustainability initiatives, sustainability reputation and the adoption of environmental management system practices through ISO 14001 certification. Previous literature has revealed that those metrics are positively related to supplier sustainability performance (Naffin et al, 2023;F. Yang & Zhang, 2017;Zimmer et al, 2016).…”
Section: 2measuresmentioning
confidence: 99%
“…Beyond this, SSCM serves as an approach for buying firms to manage sustainability concerns with suppliers in the form of supplier evaluation for risk and performance (Chowdhury & Quaddus, 2021). To assess sustainability performance of suppliers, the most common tools suggested to buying firms are certifications, sustainability report and codes of conduct (Naffin et al, 2023). However, implementing SSCM requires more than just supplier evaluation.…”
Section: Introductionmentioning
confidence: 99%